Winking at Humanitarian Neutrality: The Liminal Politics of the State in Lebanon - Carpi, Estella (Anthropologica, 2019)
Drawing on the July 2006 Israel–Lebanon War in Beirut’s southern suburbs and the Syrian refugee influx into the villages of Akkar in northern Lebanon, I suggest that the Lebanese state aspires to officially assert itself as a liminal space in a bid to survive crises and preserve its political capital, therefore aborting the attempts made by citizens and refugees to leave such liminality. I look at how professed state liminality meets with humanitarian neutrality, which is a principle of several international humanitarian agencies that assisted the internally displaced in 2006 and Syrian refugees from 2011 in Lebanon. Although in anthropology liminality has mostly been approached as anti-structural and an embodiment of the margins, by proceeding from people’s perception of state enmity and their frustrated aspirations to befriend the state, I suggest that state liminality rather captures the structural peculiarity of the Lebanese state’s agency and violent presence, made of repressive and neglectful politics.